Otimização de esforços longitudinais de FPSO’s e petroleiros - Silva, Rodrigo Gomes da (2019)
This thesis brings a method to solve the problem of loading and unloading liquid bulks on ships and FPSO’s making it is possible to carry out a linear optimization process of tank filling aiming for smaller structural efforts. The SIMPLEX method was used to carry out the linear optimization search for the best solution of the equations system developed. The SSTAB program was used for verifying, validating, to make the equilibrium and strength analysis of the chosen vessel. As result the proposed method is applied on an actual loading sequence in order to create a new loading sequence that achieves the same equilibrium conditions with lesser structural efforts.